Uma contribuição à estimativa de indicadores de desempenho do estado operacional de cabos isolados sob a ação das arborescências - Lima, Fernando Nogueira de (2008)
Distinct matters related to power quality challenges represent areas of growing interest for the electric engineering community. By considering the subject of power supply with quality and reliability, the continuity of the supply appears as a very important task to be fulfilled. As a matter of fact, the occurrence of failures in components and installations, in special those related to the misoperation of power cables, emerges as a relevant point to be tackled. Within this context arises the insulation degradation due to the known water treeing phenomenon. This effect has been reported as a cause for precocious aging of insolated cables and subsequent impacts upon the dielectric material. Focusing this subject, this thesis aims at presenting a methodology for estimating the actual operational conditions of a given insolated cable by the loss current analysis. The technique here employed is based upon time domain representation and uses the Fourier decomposition for identification of the harmonic contribution of the currents involved from which the methodology provides means to establishing insulation state indicators so as to forecast information about the cable life expectance conditions.